2002
DOI: 10.1046/j.1540-8191.2002.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fibrin Injection to Promote New Collateral Growth in Hind Limb Ischemia in a Rabbit Model

Abstract: Intramuscular injection of a fibrin meshwork considerably increased angiogenesis in the severely ischemic hind limb and may be strongly recommended for clinical use in patients with limb-threatening ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…32 The therapeutic effects of fibrin on hindlimb ischaemia they reported are consistent with those of the present study. However, the fibrin preparations used in the two studies are different.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…32 The therapeutic effects of fibrin on hindlimb ischaemia they reported are consistent with those of the present study. However, the fibrin preparations used in the two studies are different.…”
Section: Discussionsupporting
confidence: 92%
“…Chekanov et al used a fibrin sealant that formed a meshwork when applied to the ischaemic tissue. 32 The fibrin meshwork is a mixture of cross-linked fibrin, unreacted fibrinogen, thrombin and fibrinogen peptide A and B cleaved from fibrinogen by thrombin, which is angiogenic. 33 Therefore, the therapeutic effects of the fibrin gel may have come from the synergistic effects of multiple compounds.…”
Section: Discussionmentioning
confidence: 99%
“…39 Accordingly, intramuscular injection of fibrin matrices promoted arteriogenesis in a rabbit hindlimb ischemia model. 40 On the other hand, many cellular actions of thrombin are regulated by mechanisms apart from its role in coagulation cascade. Thrombin is clearly accepted as the principal physiologic regulator of PAR1 and PAR4, 41 particularly in terms of targeting the cardiovascular system and inflammation, which is an early key process for ischemia-induced angiogenesis and arteriogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of fibrin alone to re-establish blood supply in ischemic tissue has been well documented [43][44][45]. Christman et al [43] reported that injection of a fibrin hydrogel into the ischemic myocardium one week after induction of MI in a rat model of ischemia-reperfusion method showed significant improvement in cardiac function and infarct wall thickness.…”
Section: Hydrogels In Therapeutic Angiogenesismentioning
confidence: 99%
“…Efficiency of fibrin hydrogels in promoting neovascularization was shown in rabbit models of hindlimb ischemia [44,45]. Angiography assessment at day Angiogenic factors have also been incorporated into fibrin through various methods; the most common one is physically mixing these factors with fibrinogen and thrombin during coagulation [46][47][48][49].…”
Section: Hydrogels In Therapeutic Angiogenesismentioning
confidence: 99%